Quercetin & Ethanol Attenuate the Progression of Atherosclerotic Plaques with Concomitant Up Regulation of Paraoxonase1 (PON1) Gene Expression and PON1 Activity in LDLR(-/-) Mice - Leckey, Leslie C. (2010)
BACKGROUND: Since moderate wine drinking is atheroprotective it is clinically relevant to elucidate its possible mechanism/s of action/s. Our objective is to demonstrate the potential benefits of the wine components, quercetin and ethanol, on the development of aortic plaques with parallel changes in antiatherogenic factors. METHODS AND RESULTS: The effects of quercetin and ethanol on the development of aortic atherosclerotic lesions, liver PON1 gene expression, and serum PON1 activity were measured in LDLR(-/-) mice on an atherogenic diet for 4-weeks and 8-weeks. Depending on the duration and dosage of these modulators, 12.5-25 mg/dl quercetin (12.5Q-25Q) and 18-25% ethanol, the magnitude of decreases in aortic lesions caused by moderate ethanol and quercetin ranged from 20-70% (p<0.05-p<0.001) based on ultrasound biomicroscopy (UBM) analyses, and from 18-61% (p<0.05-p<0.001) based on morphometric analyses. The composite plot of all the UBM and morphometric data showed significant correlation between these two methods (p = 0.0001, Pearson r = 0.79 for 4-weeks treatment; p = 0.000004, Pearson r = 0.84 for 8-weeks treatment). Concomitantly, 4-week treatments with 12.5Q and 18% ethanol up regulated liver PON1 mRNA by 41% (p<0.05) and 37% (p<0.05), respectively, accompanied by 92% (p<0.001) and 61% (p<0.001) increases in serum PON1 activity, respectively. The corresponding values after 8-weeks treatment with 12.5Q and 18% ethanol were 23% (p<0.05) and 40% (p<0.02) with respect to the up regulation of liver PON1 mRNA expression while the stimulations of serum PON1 activity were 75% (p<0.001) and 90% (p<0.001), respectively. CONCLUSIONS: Based on these findings, we conclude that quercetin and moderate ethanol significantly inhibit the progression of atherosclerosis by up regulating the hepatic expression of the antiatherogenic gene, PON1, with concomitant increased serum PON1 activity.